Soil organic carbon stocks in a tidal marsh landscape are dominated by human marsh embankment and subsequent marsh progradation. (3rd December 2018) - Van de Broek, M.; Baert, L.; Temmerman, S.; Govers, G.
Summary: Tidal marshes are coastal and estuarine ecosystems that store large amounts of sedimentary organic carbon (OC). Despite the valuable ecosystem services they deliver, tidal marshes have been converted to other land‐use types over the past centuries. Although previous studies have reported large decreases in soil organic carbon (SOC) stocks after tidal marsh embankment, knowledge on the magnitude and rate of OC losses is still limited. Here, we studied the effect of stepwise embankments of brackish and salt marshes and subsequent marsh progradation on SOC stocks in the Scheldt estuary (the Netherlands). We collected samples from soil profiles along tidal marsh–reclaimed tidal marsh chronosequences and determined total OC stocks and the stable carbon signature of the OC. Our results showed that large losses of previously sequestered SOC occur on a decadal timescale with the embankment of brackish (−8.7 ± 0.7 kg OC m −2 ) and salt marshes (−6.7 ± 0.8 kg OC m −2 ). The (incomplete) replacement of tidal marsh OC by agricultural OC is substantially faster in topsoils (ca. a century) compared with subsoils (multiple centuries). Simulations with a coupled land use–SOC model showed that large rates of marsh progradation following embankment construction resulted in a substantial increase in landscape‐scale SOC storage, whereas large SOC losses occurred in landscapes dominated by embanked tidal marshes. The findings of our study might help to assess how these management practices affect regional SOC stocks. Highlights: We studied how OC stocks in tidal marsh sediments are affected by embankment construction OC stocks of both brackish and salt marsh sediments were reduced by ca. 60% with embankment Gains in landscape‐scale SOC storage occurred with marsh progradation after embankment If no marsh progradation occurs, embankments always lead to SOC loss at the landscape scale